An urban oriented and multilayered experience on architectural education in (the global world) - Manisa, Kunter (ELSEVIER SCIENCE BV, 2012)
Conventional education has come to be discussed in a formation of global world in which borders between professions become obscure by stratification of intelligence and their interests intersect with each other. Rapid renewal of knowledge and the help of communication facilities for the produced information to be shared instantly recognized an order of life that professionals live in a lifelong education and development. Architecture is fed by the accumulation of knowledge from many disciplines due to the nature of itself. The most important subject in architectural education for the students is to be fed up by these interests and to have the ability (skill) to produce correct relationship between these fields in planning and design and to produce decisions. From that point of view, several diploma projects was held in a number of selected fields with different variables in corporations with local governments at Yildiz Technical University, Faculty of Architecture between the years of 2004 to 2009. In the scope of the studies, Interdisciplinary research, analytical approach, synthesis, planning and design process based studies were carried out at 6 different studios in which organizational structure and fieldworks were determined with the local governments. According to the studios, Architectural and planning-oriented, but in sociology, psychology, economics, environmental science, archaeology, art history feeding project was carried out in different areas at the same time. Project process and outputs were assessed with predetermined evaluation criteria in juries (exams) with the participation of local governments. The project studies, processes and outputs over the results were evaluated and interpreted in the paper.
Keywords: Design Theories; Architectural Design; Case based instructions; multi-diciplinary education; Education & Educational Research